2015
DOI: 10.1007/s11104-015-2607-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid plant rehydration initiates permanent and adverse changes in the photosynthetic apparatus of triticale

Abstract: Background and aims The reasons for partial recovery after a soil drought are not fully understood and have not been studied so far. This study investigated the physiological and biochemical responses of triticale cultivars with differential recovery ability after soil water deficit. Methods Activity of the photosynthetic apparatus under soil drought followed by rehydration was estimated. Plant antioxidant potential was determined based on the measurement of catalase and peroxidase activity. The levels of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 90 publications
(90 reference statements)
1
12
0
1
Order By: Relevance
“…Increases in ROS levels under water deficit conditions are associated with low efficiency in the excitation energy dissipation, through the photosynthetic apparatus, which it is considered an important source of overproduction of ROS under abiotic stress (Hura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in ROS levels under water deficit conditions are associated with low efficiency in the excitation energy dissipation, through the photosynthetic apparatus, which it is considered an important source of overproduction of ROS under abiotic stress (Hura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The short vegetation period of spring cereals is often insufficient for full plant recovery after drought. A common reason for incomplete recovery is permanent damage to the photosynthetic apparatus caused by leaf dehydration (Hura et al 2015).…”
Section: Cereal Research Communications 47 2019mentioning
confidence: 99%
“…This outcome could explain such a substantial drop in the carbohydrate content in the leaves of PA15 plants under thermal stress. Hura et al (2015) found a correlation between ψR0 and φR0 and hydrogen peroxide production as an effect of drought stress in triticale leaves.…”
Section: CVmentioning
confidence: 86%